La via del fascismo è lastricata di buone intenzioni: Rapporti e conflitti fra le istituzioni di ricerca scientifica e il regime - Paoloni, Giovanni (Chimica nella Scuola, 2022)
The relationship of scientific research institutions with Fascism was influenced by the educational reform adopted in 1923 on the proposal of Giovanni Gentile. The fascist restructuring of public institutions, based on the same principles of the educational reform, also involved universities, academies and research agencies. After facing some early problems, the Mussolini government showed to the scientific community by alternating coercive tools with consensus awarding and exhibited a technocratic vocation.